Building Bridges for “Palliative Care-in-Place”: Development of a mHealth Intervention for Informal Home Care - Laranjeira, Carlos; Dixe, Maria Anjos; Martinho, Ricardo; Rijo, Rui; Querido, Ana (Frontiers in Psychology, 2022)
Background: In Palliative Care (PC), family and close people are an essential part of provision of care. They assume highly complex tasks for which they are not prepared, with considerable physical, psychological, social, and economic impact. Informal Caregivers (ICs) often falter in the final stage of life and develop distress, enhancing emotional burden and complicated grief. The lack of available and accessible in-person counselling resources is often reported by ICs. Online resources can promote early access to help and support for patient-IC dyads in palliative care. The primary aim of this research is to co-design, develop and test the feasibility of the Help2Care-PAL mHealth app that addresses the needs of ICs of palliative patients cared for at home. This Digital Health Intervention (DHI) in palliative care will be used for education, symptom management, communication, and decision-making, to enhance Quality of Life (QoL) of patients and ICs, fostering anticipatory grief and the reach and efficiency of services. Methods: This study will use an iterative co-design process and convergent mixed-methods design, following the MORECare consensus for developing a complex intervention. Construction of the DHI will follow four main phases: (I) a needs assessment (a cross-sectional survey, individual interviews with ICs, and focus groups with professionals with community palliative care experience); (II) design and co-production of mHealth materials and interventions to support ICs; (III) the development of a mHealth app; and (IV) usability and feasibility of the mHealth app. The Help2Care-PAL platform seeks to build resources from the perspectives and needs of both family dyads and nursing professionals working in the field of community palliative care. User-centeredness will be ensured by the active participation of patient-IC dyads and professionals of the palliative care community. Discussion: This mixed-method study will offer new insights on needs and expectations of patient-IC dyads and nurses in community palliative care regarding caregiving preparedness and online health resources. Through the implementation of an adaptive digital tool, we aim to improve access to palliative care family support, which is highly linked with the well-being of patients and especially new ICs.